2012
DOI: 10.1007/s10965-011-9792-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun nanofibers of a degradable poly(ester amide). Scaffolds loaded with antimicrobial agents

Abstract: Electrospinning conditions were evaluated to prepare micro/nanofibers of a biodegradable poly(ester amide) constituted by L-alanine, 1,12-dodecanediol and sebacic acid. 1,1,1,3,3,3-Hexafluroroisopropanol appeared as the most appropriate solvent to obtain fibers in a wide range of electrospinning conditions that allowed tuning the final diameter size. Fiber diameter increased with the flow, distance between the needle tip and the collector and decreasing voltage, which made it possible to obtain homogeneous fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…This expected result is consistent with the lack of bactericidal activity of PLA, P3TMA and IBU. In contrast, halos of inhibition were observed for PLA-P3TMA electrospun fibers loaded with TCS, CHX and CIP, evidencing the antimicrobial activity of these drugs [36,56,57,60]. The formation of such Figure 11.…”
Section: Evaluation Of Bactericide Activity Of 2:1mentioning
confidence: 96%
See 1 more Smart Citation
“…This expected result is consistent with the lack of bactericidal activity of PLA, P3TMA and IBU. In contrast, halos of inhibition were observed for PLA-P3TMA electrospun fibers loaded with TCS, CHX and CIP, evidencing the antimicrobial activity of these drugs [36,56,57,60]. The formation of such Figure 11.…”
Section: Evaluation Of Bactericide Activity Of 2:1mentioning
confidence: 96%
“…Furthermore, the release of CHX in PBS-EtOH was also very fast, reaching a value of 70% after only seven hours of exposure (Figure 11b). Previous studies [56][57][58] indicated that the release kinetics of these drugs can be explained by the Higuchi and first-order models, which are usually combined to describe the first (from the beginning to 60%) and second (40-100%) stages of the release [59], respectively. In both cases, the delivery process is explained by the diffusion of the drug through the polymer matrix, which is facilitated by the ethanol-induced swelling of PLA [36].…”
Section: Drug Release Studymentioning
confidence: 99%
“…They are widely employed for many applications such as sutures, materials for tissue regeneration, orthopedics, scaffolds and systems for controlled release of drugs in medicine [7][8][9][10][11][12]. The great interest in PLA based bionanocomposites is directly supported by the significant increase in the number of derived scientific publications [13], which clearly demonstrates an improvement of biodegradation rate and mechanical, thermomechanical and gas barrier properties [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The diffused ESR spectrum of 4-amino-TEMPO also proved homogenous dispersion of the drug at molecular level. As evident from all these properties discussed above, electrospun PEA [66], with permission from Springer).…”
Section: Nitroxylradical Incorporated Electrospun Peamentioning
confidence: 99%